Interactive Multimedia Research Trends in Higher Education: A Review of Assisted Literature NVivo 12 Pro - Hasanuddin, Hasanuddin; Asgar, Hari; Jayadi, Agus (ISB Atma Luhur, 2023)
The rapid use of technology in lecture activities, especially the use of interactive multimedia since the pandemic conditions and until now, has attracted researchers to comprehensively analyze patterns of interactive multimedia utilization. This study aims to provide information on the pattern of interactive multimedia utilization and its development to date. The research method adopted a qualitative design, through a review of various studies from 2020 to 2023, and a literature search using the free Publish or Perish program. Further reduction and screening processes were carried out using the PRISMA method. The final results of the articles that have been selected are then mapped and codified with NVivo Pro 12 program, including the development and use of interactive multimedia in universities. In the development of interactive multimedia in the university, literature is grouped into forms of interactive multimedia and tools in designing interactive multimedia. The use of interactive multimedia in institutions is grouped into two, including the types of interactive multimedia used and how the impact of the use of interactive multimedia on lecture activities. Results obtained 1) Multimedia forms developed in universities include E-modules, Software, Websites, Android applications, Autoplay, Classpoint, E-learning, and tutorial models; 2) equipment in designing interactive multimedia including Kwisoft Flopbook Maker, live streaming, Macromedia Flash, Microsoft Way, Moodle, Adobe Flash Professional CS6.5, App Inventor 2, Autocad, Power Point, and Courselab 2.4; 3) types of interactive multimedia used in learning activities in universities include Android applications, Macromedia Flash, Lectora Inspire software, Adobe Flash, Adobe Premiere, and E-learning; 4) The effect of interactive multimedia on lecture activities can increase interest or motivation, also have an impact on student achievement.